BIOCULT. Un centro multidisciplinare di ricerca applicata - Bindi, Letizia (Antropologia Pubblica, 2024)
Since 2015 the BIOCULT Center of Research has been created at the University of Molise, radically multidisciplinary-based, but above all oriented from the very beginning of its activities to work on the regional territory, first, collaborating to enhance local sustainable development processes and cultivated biodiversity, to safeguard and valorize local cultural landscapes, committed with the regeneration of rural and peri-urban contexts, with particular reference to fragile, marginal or peripheral, and depopulated areas. The center developed an intense research activity in the local dimension (community maps, shared planning, support to processes of conservation and enhancement of bio-cultural heritages, inventories and participatory platforms for the return of shared cultural practices in different contexts, etc.). This paper aims to reflect on this formula of the Research Center for the development of a more effective action of public engagement with the territories. A powerful element of such a third mission-oriented action is represented by multidisciplinary approach - linking together social sciences, heritage studies with rural economy, social innovation, law, agricultural and biosciences – and the design of researchaction projects enabling the contamination of different methodologies and a proactive involvement of local actors in their different, composite and often fragmentary components.